Differential capacitor sensor of wireless sensor network for landslide monitoring - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Hossain, M. Z. (2014)
Every year all over the world, many lives and properties are lost due to many geological catastrophes like, landslide or land-slip. Manual and electronic monitoring systems are used to predict the landslide happening period. The manual monitoring system is laborious and not practicable, then again, most of the electronic systems are complex and expensive. To monitor the natural disasters, a detecting system faces a lot of harder conditions. Natural tragedy occurs unexpectedly and damages the instrument system as well. The sensor system should be planned as a spread network with a simple positional identification device such as RFID. In addition, the network should have self-recovery, self-directed operation and actual data transmission facility in urgent situations. A distributed node network needs lot of sensors with complex structure and it is expensive too. This paper describes a simple and low cost system which comprises an underground pretension cable with a capacitor gage sensor attached at one end. A wireless sensor network has been proposed for a simple landslide monitoring system using RFID. The sensing node network can be operated by initializing mode, measuring mode and urgent mode depending on the situation. A switching mechanism is used to switch automatically to any one of these operating modes which makes a robust and dynamic control of data transmission system. A mathematical model has been developed for the system and verified by simulation. The result shows that an early prediction of the landslide is possible by using the proposed system.